Dose-dependent expression of CLIP2 in post-Chernobyl papillary thyroid carcinomas. (28th May 2015) - Selmansberger, Martin; Kaiser, Jan Christian; Hess, Julia; Güthlin, Denise; Likhtarev, I.; Shpak, Victor; Tronko, Mykola; Brenner, Alina; Abend, Michael; Blettner, Maria; Unger, Kristian; Jacob, Peter; et al.
Summary: This study showed a clear dose-response relationship for the CLIP2 radiation marker in post-Chernobyl papillary thyroid carcinoma cohorts for young patients and hints to different molecular mechanisms in tumors induced at low doses compared to moderate/high doses. Abstract: A previous study on papillary thyroid carcinomas (PTC) in young patients who were exposed to 131 iodine from the Chernobyl fallout revealed an exclusive gain of chromosomal band 7q11.23 in exposed cases compared to an age-matched control cohort. CLIP2, a gene located within band 7q11.23 was shown to be differentially expressed between exposed and non-exposed cases at messenger RNA and protein level. Therefore, a standardized procedure for CLIP2 typing of PTCs has been developed in a follow-up study. Here we used CLIP2 typing data on 117 post-Chernobyl PTCs from two cohorts of exposed patients with individual dose estimates and 24 non-exposed controls to investigate a possible quantitative dose-response relationship of the CLIP2 marker. The 'Genrisk-T' cohort consisted of 45 PTCs and the 'UkrAm' cohort of 72 PTCs. Both cohorts differed in mean dose (0.59 Gy Genrisk-T, 1.2 Gy UkrAm) and mean age at exposure (AaE) (2 years Genrisk-T, 8 years UkrAm), whilst the median latency (16 years Genrisk-T, 18 years UkrAm) was comparable. We analyzed the association between the binary CLIP2 typing and continuous thyroid dose with logistic regression. A clear positive dose-response relationship was found for young PTC cases [age at operation (AaO) < 20 years, AaE < 5 years]. In the elder age group a higher proportion of sporadic tumors is assumed due to a negligible dose response, suggesting different molecular mechanisms in sporadic and radiation-induced cases. This is further supported by the association of elder patients (AaO > 20 years) with positivity for BRAF V600E mutation.